Local rhamnosoft, ceramides and L‐isoleucine in atopic eczema: a randomized, placebo controlled trial. Issue 3 (13th January 2014) - Marseglia, Alessia; Licari, Amelia; Agostinis, Fabio; Barcella, Antonio; Bonamonte, Domenico; Puviani, Mario; Milani, Massimo; Marseglia, GianLuigi
Abstract Background A non‐steroidal, anti‐inflammatory moisturizing cream containing rhamnosoft, ceramides, and L‐isoleucine (ILE) (pro‐AMP cream) has been recently developed for the specific treatment of atopic eczema (AE) of the face. In this trial, we evaluated the clinical efficacy and tolerability of pro‐AMP cream in the treatment of facial AE in children in comparison with an emollient cream. Methods In a randomized, prospective, assessor‐blinded, parallel groups (2:1) controlled trial, 107 children (72 allocated to pro‐AMP cream and 35 allocated to control group) with mild‐to‐moderate chronic AE of the face were enrolled. Treatments were applied twice daily for a 6‐week period. Facial Eczema Severity Score (ESS) was evaluated at baseline, week 3, and week 6, by an assessor unaware of treatment allocation. Investigator's Global Assessment (IGA) score was assessed at week 3 and at week 6. Tolerability was evaluated at week 3 and at week 6 using a 4‐point score (from 0: low tolerability to 3: very good tolerability). Results At baseline ESS, mean (SD) was 6.1 (2.4) in the pro‐AMP cream group and 5.3 (3) in the control group. In the pro‐AMP group, in comparison with baseline, ESS was significantly reduced to 2.5 (−59%) after 3 wks and to 1.0 (−84%) at week 6 (p = 0.0001). In the control group, ESS was reduced to 3 (−42%) at week 2 and to 2.6 (−50%) at week 6. At week 6, ESS in pro‐AMP cream was significantly lower than the control group (1.0 vs. 2.6; p = 0.001). Both products were well tolerated. Conclusion Pro‐AMP cream has shown to be effective in the treatment of mild‐to‐moderate chronic lesion of AE of the face. Clinical efficacy was greater in comparison with an emollient cream. (Clinical trial Registry: NTR4084).